1996
DOI: 10.1002/eji.1830261033
|View full text |Cite
|
Sign up to set email alerts
|

Purified human peripheral blood basophils release interleukin‐13 and preformed interleukin‐4 following immunological activation

Abstract: Recent studies have shown that human basophils, like mast cells, generate interleukin (IL)-4 following immunological activation and may thus participate in late-phase allergic and inflammatory processes. Here, we report the capacity of human basophils to release IL-13 within 24 h following stimulation with anti-IgE. Additionally, in 14 out of 31 experiments, we observed that basophils rapidly release performed IL-4 within 5-10 min, as well as newly generated IL-4, which was released 4 h following stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
110
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 26 publications
10
110
1
Order By: Relevance
“…Moreover, because basophils have preformed IL-4, these cells can release IL-4 very quickly in response to an appopriate stimulus. Although we have demonstrated that basophils release IL-4 as quickly as 2 h after exposure to BmAg (the shortest time period we evaluated), basophils have been documented to release IL-4 within 5-10 min of IgE cross-linking (13). Also, because basophils can maintain IgE-mediated memory for at least 1 mo even in the absence of ongoing de novo IgE production (29), basophils may be responsible for quickly re-establishing a Th2 response against future filarial exposures in patients who have been infected previously with filariae.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, because basophils have preformed IL-4, these cells can release IL-4 very quickly in response to an appopriate stimulus. Although we have demonstrated that basophils release IL-4 as quickly as 2 h after exposure to BmAg (the shortest time period we evaluated), basophils have been documented to release IL-4 within 5-10 min of IgE cross-linking (13). Also, because basophils can maintain IgE-mediated memory for at least 1 mo even in the absence of ongoing de novo IgE production (29), basophils may be responsible for quickly re-establishing a Th2 response against future filarial exposures in patients who have been infected previously with filariae.…”
Section: Discussionmentioning
confidence: 83%
“…Although this may be a valid finding, it is also possible that the conditions we used were insensitive for the detection of IL-13. In particular, we may have used insufficient duration of cell culture time, as IL-13 release from basophils may not peak until at least 24 h after basophil activation (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive IL-4 transcripts, moreover, are potentially required to replenish intracellular stores of preformed IL-4 protein in basophils (Figs. 2C and 8C) (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Basophils could enhance Th2-associated immune responses since they release IL-4 within minutes of activation. 11,12 Activation can occur by crosslinking of surface-bound IgE molecules or by a large variety of substances in an antigen-unspecific manner (reviewed in Falcone et al 2 ). Mast cells and basophils express constitutively low levels of IL-4, which can be visualized by using sensitive IL-4 reporter mice expressing enhanced green fluorescent protein (eGFP) under control of regulatory elements of IL-4 (4get mice 13 ).…”
mentioning
confidence: 99%